Earthworms in the conversion of natural grasslands to agropastoral systems—a preliminary study in Vale Verde, Rio Grande do Sul, Brazil - de Santo, Fernanda B.; Niemeyer, Júlia C.; Bartz, Marie L. C. (Zootaxa, 2023)
Soils, in addition to supporting agricultural production, are the source of a wide diversity of essential ecosystem functions and services performed by invertebrate organisms. Earthworms play a key role as ecosystem engineers, but little is known about the diversity of the state of Rio Grande do Sul, Brazil, and even less concerning land-use conversion scenarios. Earthworms were sampled using the TSBF method in natural grassland (NG1) in July 2018 and subsequently converted to soybean in an agropastoral system (AP) in December 2018 and July 2019. In July 2019 a nearby natural grassland (NG2) was also sampled and considered as a reference. The earthworms were identified to family, genus and/or species, and the total number of individuals and proportion of native and exotic species were calculated and presented. A total of 583 individuals were collected and seven species were identified: three native species—Kerriona sp.7, Kerriona sp.8, Eukerria rosea; and four exotic/peregrine species—Amynthas corticis, Dichogaster bolaui, Bimastos parvus, Pontoscolex corethrurus. The two native Kerriona species are new to science and were found after the conversion of the area. The other native species (Eukerria rosea), also found after the conversion, had a high number of individuals in the last sample. The results can be related to the availability and changing of resources, due to the conversion of the land use with a high rain preceding the winter season.